Phytochemical Analysis And In Vitro Antioxidant Activity From The Extract Of Bacopa Monnieri (L.) Pennel - A Multipurpose Medicinal Plant - B.SUBASHRI; Y. JUSTIN KOILPILLAI (International Journal of Pharma and Bio Sciences, 2012)
Bacopa monnieri, an important medicinal plant belonging to the family of Scrophulariaceae, which has been valued for centuries in Ayurvedic medicine, was extracted with ethyl acetate and methanol solvents for the purpose of preliminary screening .The different qualitative chemical tests were performed on the extracts to detect the various phyto constituents or antioxidants present in them. The photochemical screening reveals the presence of many therapeutically important compounds such as glycosides, alkaloids, saponins, phenols, proteins and carbohydrates. Since the phenolic compounds have remarkable antioxidant activities, our present work aims at evaluating the antioxidant activities by the three in vitro models such as DPPH free radical scavenging activity, ferric thiocyanate (FTC) and Thiobarbituric acid (TBA) method. From the present investigative phytochemical analysis of Bacopa monnieri plant extract it is revealed that the antioxidant activity of the plant material is due to the presence of phenolic compounds.